Bank Interest Rates and Deposit Growth in Nepal (The Journal of Economic Concerns, 2022)
Nepalese banking is characterized by the fragmented system where different classes of banks and financial institutions operate simultaneously. Recently, sluggish deposit growth leads to tighter Credit to Deposit Ratio (CD-ratio) and banks suffer from deficit of loanable funds. Immediate response of banks at the time of shortfall of deposit is increasing deposit interest rate. Does bank’s strategy of increasing deposit rate work? This is key question of this paper. This study aims to find the interest elasticity of bank deposit in Nepalese commercial banks. Monthly average data of deposit and interest are used for the purpose of analysis and the result shows unitary elasticity of interest rate. Bank deposit and bank’s liquid assets holding have highly significant negative relationship. This study reveals weak association of interest rate change and deposit growth. Banks are recommended to increase banking access and enhance better banking services for sustainable deposit growth.